MODEL PENYELENGGARAAN PROGRAM PENDIDIKAN KEAKSARAAN DASAR MELALUI PELIBATAN PEMERINTAH KAMPUNG DAN TOKOH AGAMA - Nanang Kristanto (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2020)
Based on data from the Central Bureau of Statistics (BPS) and the Ministry of Education and Culture's Center for Data and Statistics on Education and Culture, nationally there are still around 2.07 percent or 3,387,035 people (15-59 years) who are illiterate. Although every year the illiteracy rate has decreased, however, Papua and West Papua still have the highest illiteracy rates. The implementation of basic literacy education programs in Papua province experiences very severe challenges, geographical conditions and the availability of access to education services are problems that must be immediately get a real solution. So innovation and appropriate strategies are needed in order to answer the problem of difficult access and the availability of education services. For this, it is necessary to involve various potentials and existing elements to be able to independently organize literacy education programs. In general, this research aims to expand access and service coverage of literacy education through the model of implementing basic literacy education programs through the involvement of village government and religious leaders. This research and development was carried out with aapproach mix method using the method (Research and Development). The stages in this research are: 1). Preliminary study, 2). Modeling 3) Modeling Tests 4) Model Validation, Data is collected through in-depth interviews, documentation, and literacy studies. then analyzed and processed by reducing data, grouping data, and interpreting the data. Data analysis was carried out descriptively. This research and development was carried out in Keerom Regency and Jayapura city which covers 3 districts in Keerom Regency which consists of 4 villages. Kampung, Yowong, Kampung Wambes, Ubiyau Village, Alang-Alang 5 Village and one district in the City of Jayapura, namely in the village of Mother Maria. All villages that were research and development locations were villages with indigenous Papuans. Research and development of this model was carried out for 9 months starting from March to November 2019. The model for implementing the basic literacy program through the involvement of village governments and religious leaders was effective. there is no non-formal education unit. This model is able to provide guidance for village governments to independently carry out basic literacy programs. The village government as the organizer of this model is expected to be able to collaborate with various village figures and officials, so that the implementation of this model can be financed independently by the village government. The Education Office / SKB / SNPF can more optimally carry out its role as a driving force and person in charge as well as monitoring and supervision so that this model can continue and achieve its goals. AbstrakBerdasarkan data dari Badan Pusat Statistik (BPS) serta Pusat Data dan Statistik Pendidikan dan Kebudayaan Kemendikbud, secara nasional masih ada sekitar 2,07 persen atau 3.387.035 jiwa (15-59 tahun) yang buta aksara. Walaupun setiap tahun angka buta aksara mengalami penurunan, namun, untuk wilayah Papua dan Papua Barat masih menjadi yang tertinggi angka buta aksaranya, Penyelenggaraan program pendidikan keaksaraan dasar di provinsi Papua mengalami tantangan yang sangat berat, kondisi geografis serta ketersediaan akses layanan pendidikan menjadi masalah yang harus segera mendapatkan solusi nyata. Maka diperlukan inovasi serta strategi - strategi yang sesuai agar dapat mejawab masalah sulit akses serta kertesedian layanan Pendidikan .Untuk itu perlu melibatkan berbagai potensi dan unsur yang ada untuk dapat secara mandiri menyelenggarakan program Pendidikan keaksaraan. Secara umum Penelitian ini bertujuan untuk memperluas akses dan jangkaun layanan pendidikan kekasaraan melalui model Penyelenggaran program pendidikan keaksaraan dasar melalui pelibatan pemerintah kampung dan tokoh agama. Penelitian dan pengembangan ini dilakukan dengan pendekatan Mix methodemengunakan motode (Research and Development). Tahapan dalam penelitian ini yaitu : 1). Studi pendahuluan, 2). Penyusunan Model 3).Ujicoba Model 4).Validasi Model, Data diambil melalui wawancara mendalam, dokumentasi, serta studi literasi. kemudian dianalisis dan diolah dengan cara mereduksi data, mengelompokkan data, dan menginterpretasikan data, Analisis data dilakukan secara deskriptif. Penelitian dan pengembangan ini dilakukan di Kabupaten Keerom dan kota Jayapura yang mencakup 3 Distrik di Kabupaten Keerom yang terdiri dari 4 Kampung. kampung, Yowong, Kampung Wambes, kampung Ubiyau, Kampung Alang-alang 5 serta satu distrik di Kota jayapura yaitu di kampung Bunda Maria. Semua kampung yang menjadi lokasi penelitian dan pengembangan merupakan kampung dengan penduduk asli Papua. Penelitian dan pengembangan model ini di lakukan selama 9 bulan dimulai dari bulan Maret sampai November 2019. model penyelenggaraan program keaksaraan dasar melalui pelibatan pemerintah kampung dan tokoh agama efektif Untuk memperluas akses penyelenggaraan Keaksaraan dasar, khusus nya daerah-daerah 3T serta daerah remot area, yang tidak terdapat satuan pendidikan Nonformal. Model ini mampu memberikan panduan bagi pemerintah kampung untuk menyelenggarakan program keaksaraan dasar secara mandiri. Pemerintah Kampung sebagai penyelenggara model ini, diharapkan bisa menjalin kerjasama dengan berbagai tokoh serta perangkat kampung, agar penyelenggaraan model ini bisa dibiayai secara mandiri oleh pemerintah kampung. Dinas Pendidikan/SKB/SNPF lebih maksimal menjalankan perannya sebagai motor penggerak dan penaggungjawab sekaligus melakukan pemantauan dan pengawasan agar model ini dapat berlajan dan mencapai tujuan.